2020
DOI: 10.21608/aprh.2020.26014.1101
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Immune System in an Experimental Social Behavior Model: Review Article

Abstract: There is growing evidence supports the regulatory role of the immune system in neuronal function and mental health. Many studies have demonstrated the impact of the immune system in neurodegenerative disorders. There are beneficial therapeutic effects of targeting the immune system in the management of these disorders. However, there are gaps in the available knowledge and many steps are needed to move forward. Sensory contact model (SCM) is an experimental social behavior model which allows the formation of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 96 publications
0
1
0
Order By: Relevance
“…Furthermore, it decreased anxiety and increased exploratory tendency and curiosity [8]. It is reported that the monoaminergic hypothesis is the most accepted mechanism of depression by major depletion of brain 5HT, NE, and DA [4].Furthermore, the antioxidant and antiinflammatory impact of DDB which is extracted from Schisandra Chinensis protects against central neurodegeneration & neuroinflammation which have been reported in various CNS disorders[28][29][30][31][32]. So the antidepressant-like effect of DDB which was observed in the current study may be considered as a parallel to the observed changes in neurotransmitters and the increase in motor activity or to the decrease of anxiety as observed in the current study.…”
mentioning
confidence: 99%
“…Furthermore, it decreased anxiety and increased exploratory tendency and curiosity [8]. It is reported that the monoaminergic hypothesis is the most accepted mechanism of depression by major depletion of brain 5HT, NE, and DA [4].Furthermore, the antioxidant and antiinflammatory impact of DDB which is extracted from Schisandra Chinensis protects against central neurodegeneration & neuroinflammation which have been reported in various CNS disorders[28][29][30][31][32]. So the antidepressant-like effect of DDB which was observed in the current study may be considered as a parallel to the observed changes in neurotransmitters and the increase in motor activity or to the decrease of anxiety as observed in the current study.…”
mentioning
confidence: 99%